IDNLearn.com: Where your questions meet expert advice and community insights. Get the information you need from our community of experts who provide accurate and comprehensive answers to all your questions.

Solve the system of two equations using substitution.

1. [tex]\( y = 2 + 3x \)[/tex]
2. [tex]\( 4x - 3y = -16 \)[/tex]

A. [tex]\((-2, 4)\)[/tex]
B. [tex]\((2, 8)\)[/tex]
C. [tex]\((-2, -4)\)[/tex]
D. [tex]\((2, 10)\)[/tex]


Sagot :

Certainly! Let's solve the system of equations using substitution.

We are given two equations:
[tex]\[ \begin{array}{l} 1. \quad y = 2 + 3x \\ 2. \quad 4x - 3y = -16 \end{array} \][/tex]

Step 1: Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation. The first equation is already solved for [tex]\( y \)[/tex], so we have:
[tex]\[ y = 2 + 3x \][/tex]

Step 2: Substitute [tex]\( y = 2 + 3x \)[/tex] into the second equation:
[tex]\[ 4x - 3(2 + 3x) = -16 \][/tex]

Step 3: Distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ 4x - 6 - 9x = -16 \][/tex]

Step 4: Combine like terms on the left side:
[tex]\[ 4x - 9x - 6 = -16 \\ -5x - 6 = -16 \][/tex]

Step 5: Add 6 to both sides of the equation to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -5x = -16 + 6 \\ -5x = -10 \][/tex]

Step 6: Divide both sides by -5 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-10}{-5} \\ x = 2 \][/tex]

Step 7: Substitute [tex]\( x = 2 \)[/tex] back into the first equation ( [tex]\( y = 2 + 3x \)[/tex] ) to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 2 + 3(2) \\ y = 2 + 6 \\ y = 8 \][/tex]

Therefore, the solution to the system of equations is [tex]\((x, y) = (2, 8)\)[/tex].

So, the correct answer is:
[tex]\[ (2, 8) \][/tex]
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Thank you for choosing IDNLearn.com. We’re committed to providing accurate answers, so visit us again soon.